Social distancing: Psychological considerations and the role of technology. Issue 2 (2nd July 2020) - Siwach, Twinkle; Bhuta, Aishwarya
ABSTRACT: The COVID-19 pandemic is an unprecedented catastrophe. While the coronavirus itself can be deadly, the lockdown necessitated in its wake has taken a toll on the livelihood opportunities of the marginalized sections of the society. Apart from the obvious economic repercussions, the social and psychological impact of the lockdown must be examined. Three major themes are discussed – isolation and the self, understanding physical distancing vis-à-vis social distancing, and the downsides of the digital transformation. Being stranded somewhere or locked indoors can destabilize mental health. Besides, while physical distancing is necessary, our apathy in the form of social distancing exacerbates the distress of the socio-economically vulnerable communities worst hit by the crisis. Technology can assume a hegemonic role and cannot be an enabler unless the digital divide is bridged. This is an attempt to initiate a conversation around the ways in which the pandemic has transformed our social interactions.